A proposed new international convention supporting the rights of pregnant women and girls and their newborn infants. Issue 5 (13th January 2012) - Winrow, Benjamin; Bile, Khalif; Hafeez, Assad; Davies, Hugh; Brown, Nick; Zafar, Shamsa; Cham, Mamady; Phillips, Barbara; MacDonald, Rhona; Southall, David P
Abstract : For a multitude of eminently modifiable reasons, death rates for pregnant women and girls and their newborn infants in poorly resourced countries remain unacceptably high. The concomitant high morbidity rates compound the situation. The rights of these vulnerable individuals are incompletely protected by existing United Nations human rights conventions, which many countries have failed to implement. The authors propose a novel approach grounded on both human rights and robust evidence-based clinical guidelines to create a 'human rights convention specifically for pregnant women and girls and their newborn infants'. The approach targets the 'right to health' of these large, vulnerable and neglected populations. The proposed convention is designed so that it can be monitored, audited and evaluated objectively. It should also foster a sense of national ownership and accountability as it is designed to be relevant to local situations and to be incorporated into local clinical governance systems. It may be of particular value to those countries that are not yet on target to meet the Millennium Development Goals (MDGs), especially MDGs 4 and 5, which target child and maternal mortality, respectively. To foster a sense of international responsibility, two additional initiatives are integral to its philosophy: the promotion of twinning between well and poorly resourced regions and a raising of awareness of how some well-resourced countries can damage the health of mothers and babies, for example, through the recruitment of health workers trained by national governments and taken from the public health system.